Evaluation and Verification of the Global Rapid Identification of Threats System for Infectious Diseases in Textual Data Sources - Huff, Andrew G.; Breit, Nathan; Allen, Toph; Whiting, Karissa; Kiley, Christopher (Interdisciplinary Perspectives on Infectious Diseases, 2016)
The Global Rapid Identification of Threats System (GRITS) is a biosurveillance application that enables infectious disease analysts to monitor nontraditional information sources (e.g., social media, online news outlets, ProMED-mail reports, and blogs) for infectious disease threats. GRITS analyzes these textual data sources by identifying, extracting, and succinctly visualizing epidemiologic information and suggests potentially associated infectious diseases. This manuscript evaluates and verifies the diagnoses that GRITS performs and discusses novel aspects of the software package. Via GRITS’ web interface, infectious disease analysts can examine dynamic visualizations of GRITS’ analyses and explore historical infectious disease emergence events. The GRITS API can be used to continuously analyze information feeds, and the API enables GRITS technology to be easily incorporated into other biosurveillance systems. GRITS is a flexible tool that can be modified to conduct sophisticated medical report triaging, expanded to include customized alert systems, and tailored to address other biosurveillance needs.